An OCD patient presenting with a cerebellum venous variant in a family with a strong schizophrenia loading: a case report. - Palma, M (2012)
The role of cerebellar pathology in psychiatric symptoms has long been recognized. Cerebellar pathology has been associated with obsessive-compulsive disorder pathophysiology, particularly with compulsive hoarding. Likewise, some cerebellum abnormalities have been described in schizophrenia, as well as in comorbidity between obsessive-compulsive disorder and schizophrenia. The authors report the case of a 32-year-old woman with obsessive-compulsive disorder and a cerebellum development variant in a family with a strong schizophrenia loading. This case emphasizes the probable role of the cerebellum in the pathophysiology of both obsessive-compulsive disorder and schizophrenia, and reconsiders the existence of a so called schizo-obsessive subtype of schizophrenia.